Identification of ubiquitination-related gene classification and a novel ubiquitination-related gene signature for patients with triple-negative breast cancer - Zhao, Kankan; Zheng, Yuan; Lu, Wenliang; Chen, Bo (Frontiers in Genetics, 2023)
Background: ubiquitination related genes (URGs) are important biomarkers and therapeutic targets in cancer. However, URG prognostic prediction models have not been established in triple-negative breast cancer (TNBC) before. Our study aimed to explore the roles of URGs in TNBC. Methods: Molecular Taxonomy of Breast Cancer International Consortium (METABRIC) and gene expression Omnibus (GEO) database were used to identify URGs expression patterns in TNBC. Non-negative matrix factorization (NMF) analysis was used to cluster TNBC patients. The least absolute shrinkage and selection operator (LASSO) analysis was employed to construct multi-URG signature in the training set (METABRIC). Next, we evaluated and validated the signature in test set (GSE58812). Finally, we evaluated the immune-related characteristics to explore the mechanism. Results: We identified four clusters with significantly different immune signatures in TNBC based on URGs. Then, we developed a 11-URG signature with good performance for patients with TNBC. According to a 11-URG signature, TNBC patients can be classified into a high-risk and a low-risk group with significantly different overall survival. The predictive ability of this 11-URG signature was favorable in the test set. Moreover, we constructed a nomogram comprising the risk score and clinicopathological characteristics with favorable predictive ability. All of the immune cells and immune related pathways were higher in low-risk group than in high-risk group. Conclusion: Our study indicated URGs might interact with immune phenotype to influence the development of TNBC, which contribute to further understanding of molecular mechanism and developing of novel therapeutic targets for TNBC.